Sidesaddles and Sunbonnets: Women on the Cattle Trail - Paula Haas (Symphony in the Flint Hills, 2017)
Introduction: When you think of cattle drives up the Chisholm Trail, most likely you think of longhorns, cowboys, chuck wagons, and dust. Better add to that petticoats, sidesaddles, sunbonnets, and dolls–because sometimes, Texas women and children came along too.
Keywords: cattle drives; women; 19th century; Jack Bailey; journals